Rossby waves, extreme fronts, and wildfires in southeastern Australia. Issue 6 (24th March 2015) - Reeder, Michael J.; Spengler, Thomas; Musgrave, Ruth
Abstract: The most catastrophic fires in recent history in southern Australia have been associated with extreme cold fronts. Here an extreme cold front is defined as one for which the maximum temperature at 2 m is at least 17°C lower on the day following the front. An anticyclone, which precedes the cold front, directs very dry northerlies or northwesterlies from the interior of the continent across the region. The passage of the cold front is followed by strong southerlies or southwesterlies. European Centre for Medium‐Range Weather Forecasts ERA‐Interim Reanalyses show that this regional synoptic pattern common to all strong cold fronts, and hence severe fire conditions, is a consequence of propagating Rossby waves, which grow to large amplitude and eventually irreversibly overturn. The process of overturning produces the low‐level anticyclone and dry conditions over southern Australia, while simultaneously producing an upper level trough and often precipitation in northeastern Australia. Key Points: Catastrophic fires are associated with extreme cold fronts Extreme cold fronts are associated with propagating Rossby waves These Rossby waves appear to originate from South America